2005
DOI: 10.1016/j.immuni.2005.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Serine Protease Cathepsin G Regulates Adhesion-Dependent Neutrophil Effector Functions by Modulating Integrin Clustering

Abstract: The polymorphonuclear leukocyte (PMN)-derived serine proteases play a key role in immune complex (IC)-mediated inflammation. However, the mechanisms by which these proteases regulate inflammatory response remain largely undefined. Here, we show that IC-activated cathepsin G- and neutrophil elastase-deficient (CG/NE) PMNs adhered normally to IC-coated surfaces but did not undergo CD11b clustering and failed to initiate cytoskeletal reorganization and cell spreading. As a result, CG/NE-deficient PMNs exhibited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 50 publications
3
71
0
Order By: Relevance
“…Alpha-1-antichymotrypsin 3 plays a significant role in the inhibition of serine proteases such as cathepsin G, which is released by granulocytes during inflammation [25]. It has been shown that cathepsin G regulates the ability of PMN to stimulate other immune cells, triggering the start of local inflammatory processes [41]. Thus, low levels of alpha-1-antichymotrypsin would lead to increased presence of cathepsin G and, presumably, increase inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-1-antichymotrypsin 3 plays a significant role in the inhibition of serine proteases such as cathepsin G, which is released by granulocytes during inflammation [25]. It has been shown that cathepsin G regulates the ability of PMN to stimulate other immune cells, triggering the start of local inflammatory processes [41]. Thus, low levels of alpha-1-antichymotrypsin would lead to increased presence of cathepsin G and, presumably, increase inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils were isolated from bone marrow by a discontinuous Percoll gradient, as previously described (29). Neutrophil purity was consistently 80-90% as assessed by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…Increased integrin affinity for its ligands then permits enhanced ''outside-in'' integrin activation of downstream signalling pathways, leading to the secretion of chemokines and reactive oxygen intermediates, cytoskeletal remodelling and other inflammatory events. Cathepsin G-deficient neutrophils failed to trigger normal CD11b integrin clustering which in turn compromised Rac1 activation and the production of MIP-2 and reactive oxygen intermediates [72]. This phenotype could be rescued by addition of exogenous catalytically active cathepsin G. Its substrates remain to be identified, however.…”
mentioning
confidence: 99%